Bioequivalence of Two Tablet Formulations of Atenolol after Single Oral Administration in Healthy Volunteers - Niopas, Ioannis; Daftsios, Athanasios C; Xanthakis, Ioannis; Nikolaidis, Nicolaos; Njau, Samuel N (Arzneimittelforschung, 2000)
The pharmacokinetic parameters of two oral formulations of 100 mg tablets of atenolol (CAS 29122-68-7; Azectol® as test and another commercially available preparation as reference) were compared in an open-label, randomized, single oral dose, two-period cross-over design to 17 healthy volunteers under fasting conditions. Serial blood samples were collected prior to each administration and at 17 points within 36 h after dosing. Plasma concentrations of atenolol were measured by a validated HPLC assay with fluorometric detection. The parametric 90% confidence intervals of the geometric mean values of the test/reference ratios were 94.4% to 112.9% (point estimate: 103%) for AUC0->, 93.7% to 112.8% (point estimate: 103%) for AUC0-36, and 88.3% to 112.1% (point estimate: 100%) for Cmax, within the acceptance criteria for bioequivalence (80%-125%). Tmax values were analyzed by the nonpara-metric Wilcoxon test and the difference was not statistically significant. Therefore, it is concluded that the test and reference atenolol formulations are bioequivalent for both the extent and the rate of absorption.
Keywords: Atenolol; Azectol®, bioavailability, bioequivalence, clinical pharmacokinetics; ß-Blockers; CAS 29122-68-7